Pendampingan Pola Asuh Tahap Usia 0-6 Bulan - Siti Choirul Dwi Astuti; Rabia Zakaria (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2022)
Stunting can occur throughout the first 1000 days of a child's life. Stunting at Gorontalo Province in 2019 was 24%. One of the districts in the yellow zone in Gorontalo is Bone Bolango, with a stunting prevalence of 30%. Bone Bolango Regent Regulation Number 26 of 2020 stipulates the role of villages in stunting prevention by implementing the main target in the first 1000 days of life. The Government of Bone Bolango Regency has determined the locus of stunting villages as many as 27 villages, including Huntu Utara and South. The located in the South Bulango sub-district. This community service aims to support government programs in reducing stunting in children under five and implementing maternal and child health programs. This activity is carried out in counselling, lectures, discussions, consultations, and assistance to the people of North Huntu Village and South Huntu Village regarding parenting assistance to prevent stunting. The activity results show the growth and development of infants in the 0-6 month stage in North Huntu and South Huntu. The expected impact of the activity can be detected stunting at the age of 0-6 months so that early treatment can be carried out.